Vav Family Proteins Couple to Diverse Cell Surface Receptors - Moores, Sheri L. (American Society for Microbiology, 2000)
Vav proteins are guanine nucleotide exchange factors for Rho family GTPases which activate pathways leading to actin cytoskeletal rearrangements and transcriptional alterations. Vav proteins contain several protein binding domains which can link cell surface receptors to downstream signaling proteins. Vav1 is expressed exclusively in hematopoietic cells and tyrosine phosphorylated in response to activation of multiple cell surface receptors. However, it is not known whether the recently identified isoforms Vav2 and Vav3, which are broadly expressed, can couple with similar classes of receptors, nor is it known whether all Vav isoforms possess identical functional activities. We expressed Vav1, Vav2, and Vav3 at equivalent levels to directly compare the responses of the Vav proteins to receptor activation. Although each Vav isoform was tyrosine phosphorylated upon activation of representative receptor tyrosine kinases, integrin, and lymphocyte antigen receptors, we found unique aspects of Vav protein coupling in each receptor pathway. Each Vav protein coprecipitated with activated epidermal growth factor and platelet-derived growth factor (PDGF) receptors, and multiple phosphorylated tyrosine residues on the PDGF receptor were able to mediate Vav2 tyrosine phosphorylation. Integrin-induced tyrosine phosphorylation of Vav proteins was not detected in nonhematopoietic cells unless the protein tyrosine kinase Syk was also expressed, suggesting that integrin activation of Vav proteins may be restricted to cell types that express particular tyrosine kinases. In addition, we found that Vav1, but not Vav2 or Vav3, can efficiently cooperate with T-cell receptor signaling to enhance NFAT-dependent transcription, while Vav1 and Vav3, but not Vav2, can enhance NFκB-dependent transcription. Thus, although each Vav isoform can respond to similar cell surface receptors, there are isoform-specific differences in their activation of downstream signaling pathways.